A Combined Wetting and Scattering Study of the Near Surface Ordering in Sugar Surfactant Based Bicontinuous Microemulsions at Hydrophilic and Hydrophobic Surfaces - Wellert, Stefan; Stehle, Ralf; Micciulla, Samantha; Dahl, Margarethe; Steitz, Roland; Hellweg, Thomas; Holderer, Olaf (Frontiers in Soft Matter, 2022)
The commercial availability of natural surfactants, e.g. alkyl-oligoglucosides and the solubilization of plant and food grade oils extends the field of applications for microemulsions. To study potential effects of the confinement on the structure and dynamics inside a microemulsion, neutron reflectometry and neutron spin echo spectroscopy under grazing incidence have been used. Measurements of the contact between a bicontinuous microemulsion and a hydrophilic and hydrophobic surface are compared and show a similar wetting behavior and near surface structuring.